Amino-ether macrocycle that forms CuII templated threaded heteroleptic complexes: a detailed selectivity, structural and theoretical investigations. Issue 34 (13th April 2015) - Santra, Saikat; Mukherjee, Sandip; Bej, Somnath; Saha, Subrata; Ghosh, Pradyut
Abstract : Self-sorting behavior of a newly synthesized macrocycle with divalent metal ions and aromatic ligands via pseudorotaxane formation has been described. Abstract : A new oxy(ether)tris(amine) macrocycle, MC has been synthesized for Cu II complex formation within the cavity of the macrocyclic wheel in endotopic fashion. This complex is further reacted with the bidentate chelating ligands, 1, 10-phenanthroline (L1 ), 2, 2′-bipyridyl (L2 ), 4, 4′-dimethyl-2, 2′-bipyridyl (L3 ) and 5, 5′-dimethyl-2, 2′-bipyridyl (L4 ) to achieve the pseudorotaxanesPRT1–PRT4, respectively. These bis-heteroleptic complexes were characterized by the electrospray ionization mass spectrometry (ESI-MS), UV/Vis, EPR spectroscopy and Single-crystal X-ray structural analysis. Binding constants of the heteroleptic complexes were found in the range of 1.16 × 10 2 to 1.55 × 10 3 M −1 in acetonitrile. Further, the double level selectivity studies ofMC using different metal ions [Co II, Ni II, Cu II, Zn II ] and a number of simple bidentate chelating ligands shows the selective formation ofPRT1 that justifies the self-sorting nature of the system. Further, substitution of axles from pseudorotaxanesPRT2–PRT4 could also be achieved byL1 with nearly 100% efficiency. To corroborate the experimental studies (comparison with the crystal geometry, importance of the π–π stacking, etc .) the geometries of the pseudorotaxanes were optimized using DFT (B3LYP) in the gas phase.